A one-year longitudinal study of enterohemorrhagic Escherichia coli O157 fecal shedding in a beef cattle herd. (December 2019) - Rhades, L.C.; Larzábal, M.; Bentancor, A.; García, J. Sabio y; Babinec, F.J.; Cataldi, A.; Amigo, N.; Baldone, V.N.; Urquiza, L.; Delicia, P.J.; Fort, M.C.
Abstract: Bovines are the primary reservoir of enterohemorrhagic Escherichia coli (EHEC) O157:H7 and the main source of its transmission to humans. Here, we present a one-year longitudinal study of fecal shedding of E. coli O157. E. coli O157 obtained from recto-anal mucosal samples were characterized by multiplex PCR. The E. coli O157 prevalence ranged from 0.84% in July to 15.25% in November. The confinement within pens resulted in prevalence of 11%. Most animals (61.86%; 75/118) shed E. coli O157 at least in one sampling occasion. Of the positive animals, 82.19%, 16.44%, and 1.37% were stx positive on one, two and three sampling occasions, respectively. All the E. coli O157 isolated strains carried the genes eae and rfb O157, whereas 11%, 33% and 56% contained stx 1, stx 2 and stx 1 /stx 2, respectively. The stx 1 /stx 2 and stx 2 types were significantly higher during the grazing and finishing periods, respectively, in comparison with the rearing and grazing periods. The presence of s tx 2a subtype was evident in four isolates, whereas stx 2c was present in at least seven. However, both subtypes were present simultaneously in two isolates. The stx 1 /stx 2c, stx 1 /stx 2d and stx 1 /stx 2NT genotypes occurred in 24, 2 and 15 isolates, respectively. The simultaneous occurrence of stx 1 and stx 2c significantly increased during grazing. Some cases of within-pen and between-pen transmission occurred throughout the study. Contagion levels during in-field grazing were higher than during permanent confinement in the pens. Thus, the individual patterns of shedding varied depending on the proportion of animals shedding the bacteria within pens and the time of shedding. Highlights: Cattle fecal shedding of EHEC shows high variation along one year period Most animals shed EHEC once, in contrast to many fewer that shed twice or thrice The presence of Shiga toxin varied throughout the rearing, grazing and finishing periods The stx1/stx2c genotype was the most frequently found Within-pen and between-pen transmission occurred throughout the experiment